Pilot plant study of aqueous solution of piperazine activated 2-amino-2-methyl-1-propanol for post combustion carbon dioxide capture. (August 2016) - Rabensteiner, Markus; Kinger, Gerald; Koller, Martin; Hochenauer, Christoph
Highlights: The pilot plant allows a practical operation. Operation with real flue gases of the gas- and coal-fired power plant. Absorber and desorber have nearly industrial heights. Advantages of piperazine activated AMP over monoethanolamine can be identified. Abstract: Piperazine (PIP) activated 2-amino-2-methyl-1-propanol (AMP) (28/17 wt% AMP/PIP) was investigated in a PCC test facility on the power plant in Dürnrohr, Austria. Through the use of real power plant flue gas and the well-conceived dimensions of the test facility, industry-related conditions for full-scale applications can be assured. The specific energy consumption for solvent regeneration can be reduced to 3.15 GJ/t CO 2 (without absorber intercooler and multi-stage flash), resulting in an energy saving of 10% in comparison to 30 wt% monoethanolamine (MEA). The optimal solvent flow rate is 38% lower in comparison to that of 30 wt% MEA, resulting in less pumping demand. 28/17 wt% AMP/PIP shows a good performance especially at high flue gas flow rates because of piperazinés fast kinetics. The fast kinetics also have a positive effect in the reduction of the absorber height. Halving the absorber height still allows a performance similar to that of 30 wt% MEA. In contrast to the MEA-process, the energy demand remains constant when varying the desorber pressure.